Vocabulary of the new Europe: code words for the millennium (Pion Ltd., 2001)
Drawing upon a recent Council of Europe conference on markets and social solidarity and related interviews with financial industry elites on the prospects for pan-European pensions, this paper sets out the code words used to describe the 'new' Europe. After a century of enormous destruction and fragmentation, those now wishing to join Western Europe look towards the institutions of the European Union with hope and ambition. In doing so, the language of vision has become an essential reference point in understanding contested futures. In this context, elites are particularly self-conscious about their use of code words. These code words are especially relevant to issues such as the expanding geographical borders of Europe, the value and practice of democracy, and the apparent threat posed by Anglo-Saxon financial markets to continental nation-state social contracts. In large part, the paper is an exercise in documentation -- identifying defining and explaining the contested status of selected code words I believe to be important in the European project. But the paper is also quite contentious, theoretically speaking. In order to explain the significance of these code words, the paper begins with the relationship between words and concepts in the context of arguments by Fodor and Jackson. Here, a way is threaded between those who see words as the essence of political ideas, and those who believe words are simply the reflection of a robust material world. Political concepts are disputed, especially their relationships to one another and their place in specific institutional and geographical settings. To do so requires explaining how and why my approach goes beyond Raymond Williams's Keywords. In conclusion, implications are drawn with respect to the current debate over the likely long-term impacts of territorial incorporation for Western Europe.